Reproductive Health Concerns in Women with Systemic Lupus Erythematosus. Issue 4 (July 2015) - Kartoz, Connie Rutan
Abstract : Abstract: Women are far more likely than men to have a diagnosis of systemic lupus erythematosus (SLE), with a peak incidence during the childbearing years. Contraceptive methods and pregnancy can both adversely affect the health of women with SLE, thus careful planning and interventions are necessary to help women manage their reproductive health choices. Women with SLE may experience infertility, difficulties conceiving and maintaining pregnancy, and ultimately have less children than they had planned. Although poor health status may account for some of this disparity, inadequate counseling and management by members of the healthcare team may also be responsible. The purpose of this article is to review the pathophysiology of SLE and its effects on reproductive health, as well as to highlight recent literature supporting evidence-based practices in reproductive health counseling, nursing care during pregnancy, and monitoring for disease complications in women with SLE. Nurses play a central role in care coordination and patient education for women with SLE making decisions about family planning. Abstract : SLE has many implications for the reproductive health of women of childbearing age. The pathophysiology of SLE, its effects on reproductive health, and nursing care during pregnancy are discussed.